5-HT1A receptor: its role in the regulation of different kinds of behavior - V. S. Naumenko; E. G. Ponimaskin; N. K. Popova (Вавиловский журнал генетики и селекции)
Brain serotonin (5-HT) is known to be involved in the control of a wide range of physiological functions as well as of different kinds of behavior. Such polyfunctionality of 5-HT is mediated by numerous 5-HT receptors. Currently, 14 different 5-HT receptor subtypes expressed in the mammals have been identified. The 5-HT1А receptor is one of the most extensively characterised members of the serotonin receptor family. Increased interest to the 5-HT1А receptor is based on (1) a key role in the autoregulation of the brain serotonergic system due to the postsynaptic and presynaptic localization, (2) a great body of data demonstrating implication of 5-HT1А receptor in the control of various physiological functions (3) involvement of 5-HT1А receptors in the mechanisms of depression, anxiety and suicide. The review describes literature and original data on factors affecting the expression and functional activity of 5-HT1А receptors and the involvement of 5-HT1А receptors in the regulation of normal and pathological behavior. The structure of the 5-HT1А receptor gene is described and new data on the posttranslational regulation of 5-HT1А receptor functional activity are provided. A special focus was given to the interaction between 5-HT1А and 5-HT7 receptors followed by heterodimer formation and the role of heterodimerization in the functional inactivation of the 5-HT1А receptor. The implication of 5-HT1А receptors in the regulation of aggressive behavior, catalepsy, anxiety, depression and hibernation was shown. Special attention is focused on the involvement of 5-HT1А receptors in the regulation of 1) fear-induced aggression towards man – the basis of domestication, 2) intermale aggression underling asocial behavior in men, 3) depression and in the mechanism of antidepressant action. The described data extend the idea on the 5-HT1А receptor as a key player in the brain 5-HT system.